Shalat Alternatif Terbaik Terapi Psikoproblem - Febry, Agung Is Hardiyana; Akhmad Sahrandi (Program Studi Bimbingan dan Konseling Islam, 2021)
The modern world with quite high mobility has carved success stories materially. However, it seems that material prosperity is not enough to make his spiritual life prosperous, this is the result of the modern world's detachment from ethical, moral, traditional and religious values that have been considered obsolete. Modern humans have lost the moral aspect as a function of control and are trapped in a material cage. Modernism failed because it ignored transcendental spiritual values as the foundation of life. As a result, modern humans do not have a solid footing in building their civilization. They falter and will eventually collapse. Humans have many problems in their lives that can cause psychological problems (psychoproblems) in individuals. These psychiatric problems (psychoproblems) can have an impact on mood, mindset, and general behavior that is experienced makes you feel depressed and unable to carry out normal daily activities. The method used is content analysis. The result is that psychiatric problems (psychoproblems) or psychiatric problems can be overcome by using the approach of reality counseling and religious therapy. Individuals can ask for help from counselors to help overcome psychiatric problems (psychoproblems) by using prayer therapy to focus more on facing the future.